Cinnamomum burmannii EXTRACT AMELIORATES HIGH GLUCOSE-INDUCED BRAIN APOPTOSIS IN ZEBRAFISH EMBRYOS THROUGH INHIBITION OF PROCASPASE-9 : IN SILICO AND IN VIVO STUDY - Umi Kalsum; Husnul Khotimah; Theakirana Firdaus; Editya Fukata; Nurfaizah Titisari Sulihah; Fitrah Aulia Lisabilla; Happy Kurnia Permatasari; Sri Andarini (MNJ (Malang Neurology Journal), 2022)
Background: Brain is an organ that is prone to oxidative stress and subsequent apoptosis due to high aerobic metabolism and relatively low antioxidants, especially under hyperglycemic condition. Cinnamomum burmanii (CB) is a species that is abundant in Indonesia, therefore it is of special concern for researchers to identify the anti-apoptotic effect of CB. Objective: This study was initiated to determine the effect of CB extract on the inhibition of brain apoptosis in zebrafish embryos exposed to high glucose and to investigate its anti-apoptosis mechanism by molecular docking approach. Methods: Molecular docking was conducted to determine the interaction between several CB extracts main constituents with target protein procaspase-9, compared to control ligand Saxagliptin. Zebraﬁsh embryos were used to assess the effect of 4% glucose exposure and three doses of CB extract treatment (1.25, 5, and 10 µg/ml) on apoptosis in brain region. High-glucose condition in zebrafish embryo was confirmed with overexpression of Phosphoenolpyruvate carboxykinase (PEPCK). Apoptosis was evaluated by performing acridine orange (AO) staining and quantified by ImageJ software. Results: Molecular docking study indicated that main CB compounds, namely epicatechin, displayed stronger molecular interactions with procaspase-9 compared to control ligand Saxagliptin. There were increased numbers of apoptotic cells seen around brain region in glucose-treated group. Meanwhile, supplementation of CB extract at dose of 10 µg/ml resulted in decreased amount of apoptotic cells in brain region. Conclusion: The results suggest that CB extract protects from hyperglycemic-induced apoptosis in zebrafish embryos brain by modulating procaspase-9.